Mannose-decorated cyclodextrin vesicles: The interplay of multivalency and surface density in lectin–carbohydrate recognition - Kauscher, Ulrike; Ravoo, Bart Jan (Beilstein Journal of Organic Chemistry, 2012)
Cyclodextrin vesicles are versatile models for biological cell membranes since they provide a bilayer membrane that can easily be modified by host–guest interactions with functional guest molecules. In this article, we investigate the multivalent interaction of the lectin concanavalin A (ConA) with cyclodextrin vesicles decorated with mannose–adamantane conjugates with one, two or three adamantane units as well as one or two mannose units. The carbohydrate–lectin interaction in this artificial, self-assembled glycocalyx was monitored in an agglutination assay by the increase of optical density at 400 nm. It was found that there is a close relation between the carbohydrate density at the cyclodextrin vesicle surface and the multivalent interaction with ConA, and the most efficient interaction (i.e., fastest agglutination at lowest concentration) was observed for mannose–adamantane conjugates, in which both the cyclodextrin–adamantane and the lectin–mannose interaction is inherently multivalent.
Keywords: carbohydrates; cyclodextrins; lectins; molecular recognition; multivalency; vesicles